Farmers’ Willingness to Pay for Climate Information Services: Evidence from Cowpea and Sesame Producers in Northern Burkina Faso - Ouédraogo, Mathieu; Barry, Silamana; Zougmoré, Robert B.; Partey, Samuel T.; Somé, Léopold; Baki, Gregoire (MDPI, 2018)
Climate information is recognized as a powerful tool to reduce the effect of climate risk and uncertainty on crop production and increase the resilience and the adaptive capacity of farmers in semi-arid zones. This paper estimates farmers’ willingness to pay (WTP) for climate information within cowpea and sesame value chains in Northern Burkina Faso. The study used the contingent valuation method for a monetary valuation of farmers’ preferences for climate information. Data were collected using a structured questionnaire from 170 farmers. The study found that 63% of respondents were willing to pay for climate information services (CIS) such as seasonal climate forecast (SCF), decadal climate information (10-DCI), daily climate information (1-DCI) and agro-advisories. The predicted value for the WTP was XOF 3496 for SCF, XOF 1066 for 10-DCI, XOF 1985 for 1-DCI and XOF 1628 for agro-advisories. The study also showed that several socioeconomic and motivation factors have greater influence on farmers’ WTP for CIS. These included the gender, age, education of the farm head and the awareness of farm head to climate information. The outcomes of this paper should support policy makers to better design an efficient mechanism for the dissemination of climate information to improve the adaptive capacity of farmers to climate risks in Burkina Faso.